Analysis of the Effect of Islamic Capital Market and Islamic Banking Financing on Economic Growth in Indonesia - Putri, Salsa Erika; Mayasari, Ine (Journal of Applied Islamic Economics and Finance, 2025)
This study aims to analyze the influence of Islamic financial instruments on Indonesia’s economic growth from 2014 to 2024. The study includes Islamic stocks, sukuk, Islamic mutual funds, and Islamic banking financing. The method used is Vector Error Correction Model (VECM), which observes both short-term and long-term relationships. The results indicate that only Islamic stocks have a significant long-term positive effect on economic growth, while sukuk, mutual funds, and Islamic banking financing have yet to show significant impact. The findings suggest a need to enhance the role of Islamic financial instruments through deeper market integration and increased retail investor participation to better support national economic growth.